How Integrated Reporting Amplifies Capital Intensity to Drive Firm Value Growth? - Rosalina Angelita; Dian Saputra (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Firm value reflects performance and competitiveness, which are the main concerns for investors, especially in the consumer cyclicals sector which is sensitive to economic cycles. Inconsistencies in previous research on how working capital management and capital intensity affect firm value call for further investigation. Panel data from 83 companies selected by purposive sampling during the period 2021-2023 is used in this study. The analysis employs a moderation regression method using EViews software. The results show that capital intensity intensiveness is significantly positively related to firm value, while working capital management is not. Integrated reporting doesn't moderate the effect of working capital management on firm value, but it strengthens the relationship between capital intensity and firm value. These findings highlight the importance of investment in fixed assets and reporting transparency to increase firm value. This study provides insights for managers on leveraging integrated reporting in creating sustainable firm value.